JUVENTUDE, TRABALHO E ESCOLA: REFLEXÕES SOBRE A CONDIÇÃO JUVENIL | Youth, work and school: reflections upon juvenile condition (Trabalho & Educação, 2018)
This paper discusses some results that came from the investigation activity: “The juvenile condition of the young workers of the Brazilian Red Cross at Pampulha campus of UFMG”. The aim was to comprehend the juvenile condition of the young workers of the Brazilian Red Cross (CVB), basing on the quantitative approach, mixing it with specific techniques from the qualitative research. Theoretical bases used to develop this research came from reflections upon sociology of youth and sociology of education. Among many points of this research, we do highlight this one: the social place of those who attended the survey interferes, directly, on the possibilities of experience the juvenile condition. The condition of young people and students is marked by the worker condition. The appreciation of schooling refers to a guarantee of a better future, translated by most people as a possibility of “being someone in life”.___O artigo discute alguns resultados da investigação “A condição juvenil dos jovens trabalhadores da Cruz Vermelha Brasileira no campus Pampulha da UFMG.” Procurou-se compreender a condição juvenil dos jovens trabalhadores da Cruz Vermelha Brasileira (CVB), através de uma abordagem quantitativa mesclando-a com técnicas próprias da pesquisa qualitativa. O referencial teórico usado nesta pesquisa pautou-se em reflexões da sociologia da juventude e da sociologia da educação. Dentre os apontamentos da pesquisa, evidenciamos que o lugar social dos pesquisados interfere diretamente nas possibilidades de vivenciar a condição juvenil. A condição de jovens e de estudantes é circunscrita pela condição de trabalhador. A valorização da escolarização remete à garantia de um futuro melhor, ao que a maioria traduz como possibilidade de “ser alguém na vida”.